NURSING CARE FOR MRS. A AT RISK OF VIOLENT BEHAVIOR WITH A FOCUS ON DEEP BREATHING RELAXATION AT DR. RM SOEDJARWADI REGIONAL MENTAL HOSPITAL, KLATEN - Ika Setiani; Fida Dyah Puspasari; Sudiarto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: According to WHO (2022), there are 24 million people suffering from schizophrenia, with 3,980 of them at risk of violent behavior. The risk of violent behavior is an angry response that can manifest physically or verbally. If not addressed promptly, the risk of violent behavior can endanger both the individual and others. This condition poses a serious challenge as it can disrupt the patient’s recovery process and create anxiety in the surrounding environment. Therefore, appropriate nursing interventions are needed—not only to calm the patient but also to enhance the patient’s ability to control their emotions. One of the interventions that can be applied is the deep breathing relaxation technique. Objective: To describe the nursing care from assessment to evaluation for Mrs. A with a risk of violent behavior, focusing on the deep breathing relaxation intervention. Method: This scientific paper uses a descriptive research method in the form of a case study. Results: After three days of nursing interventions for patient with a risk of violent behavior using deep breathing relaxation, the client showed reduced tension and was able to control her emotions well. Conclusion: Deep breathing relaxation for patient was effective in reducing the risk of violent behavior.